Algorithm1 (Unique solution of the PIEPB ( ϵ , c , s ) ).

1: Input: c , s , { λ j ( 1 ) , λ j ( j ) } j = 1 n . where n = c s + 1 .

2: a 1 = λ 1 ( 1 ) .

3: For j = ( i 1 ) s + 2 , i = 1 , 2 , , c do

4: if φ j 1 ( λ j ( 1 ) ) det ( B j λ j ( j ) ) φ j 1 ( λ j ( j ) ) det ( B j λ j ( 1 ) ) = 0 then

5: ending the algorithm 1.

6: end if

7: if φ j 1 ( λ j ( 1 ) ) det ( B j λ j ( j ) ) φ j 1 ( λ j ( j ) ) det ( B j λ j ( 1 ) ) 0 then

8: computing a j , b 1 , j and ϵ 1 , j by (7) and (8).

9: end if

10: end for

11: For j = ( i 1 ) s + 3 , i = 1 , 2 , , c do

12: if φ j 1 ( λ j ( 1 ) ) φ j 2 ( λ j ( j ) ) φ j 1 ( λ j ( j ) ) φ j 2 ( λ j ( 1 ) ) = 0 then

13: ending the algorithm 1.

14: end if

15: if φ j 1 ( λ j ( 1 ) ) φ j 2 ( λ j ( j ) ) φ j 1 ( λ j ( j ) ) φ j 2 ( λ j ( 1 ) ) 0 then

16: computing a j , b ( j 1 ) , j and ϵ ( j 1 ) , j by (9) and (10).

17: end if

18: end for

19: For j = ( i 1 ) s + 4 , , i s + 1 , i = 1 , 2 , , c do

20: if φ j 1 ( λ j ( 1 ) ) φ ( i 1 ) s + 2 ( λ j ( j ) ) k = ( i 1 ) s + 4 j 1 ( λ j ( j ) a k ) φ j 1 ( λ j ( j ) ) φ ( i 1 ) s + 2 ( λ j ( 1 ) ) k = ( i 1 ) s + 4 j 1 ( λ j ( 1 ) a k ) = 0 then

21: ending the algorithm 1.

22: end if

23: if φ j 1 ( λ j ( 1 ) ) φ ( i 1 ) s + 2 ( λ j ( j ) ) k = ( i 1 ) s + 4 j 1 ( λ j ( j ) a k ) φ j 1 ( λ j ( j ) ) φ ( i 1 ) s + 2 ( λ j ( 1 ) ) k = ( i 1 ) s + 4 j 1 ( λ j ( 1 ) a k ) 0 then

24: computing a j , b ( i 1 ) s + 3 , j and ϵ ( i 1 ) s + 3 , j by (11) and (12).

25: end if

26: end for